A Method for Studying the Effects of Neurochemicals on Long-Term Compensation in Unilaterally Labyrinthectomized Rats. (1997) - Andersson, Lars; Ulfendahl, Mats; Tham, Richard
Abstract : A new method has been developed to study the influence of drugs and toxicants on longterm recovery of dynamics in the horizontal vestibulo-ocular reflex of the rat after hemilabyrinthectomy (HL). HL was performed by injecting sodium arsanilate into the middle ear. The lesion was confirmed by histology. Eye movements elicited by sinusoidal vestibular stimulation, in both light and darkness, were recorded by a search-coil technique and then analyzed by a computer program created with virtual instrument soft-ware, which calculated the gain of the slow-phase velocity (SPV) and the saccades para-meters (frequency, amplitude, and peak velocity) to the lesioned side and to the intact side separately. During the 2-10 week period after HL, repeated analysis of the spontaneous long-term recovery of such parameters revealed a slight but significant reduction of the post-HL asymmetry between SPV gain to the lesioned side and to the intact side. During the follow-up period, a post-HL increase of the phase lead remained unchanged. The reduced number of saccades/min was not completely restored. To test the usefulness of the experimental model for neurochemical investigation of such adaptation, we administered baclofen and toluene to rats 8–12 wk after hemilabyrinthectomy. Baclofen, a specific GABA B agonist, immediately restored the symmetry of SPV gain. By contrast, toluene, which has some effects on the central vestibular system that are related to GABA B transmission, aggravated the asymmetry in both the SPV gain and the number of saccades. We suggest that the experimental model would be useful for studying neurochemical mechanisms in vestibular adaptation processes.